ANALISIS PENGGUNAAN MEDIA BELAJAR, MINAT BACA TERHADAP KINERJA GURU DENGAN STRATEGI BELAJAR SEBAGAI VARIABEL MODERASI PADA DISTRIK KOKODA KAMPUNG TAROF SORONG SELATAN - Aurai, Delila; Likewati, Wa Ode; Anwar, Vebby (JURNAL LENTERA BISNIS, 2026)
This research was conducted on school teachers in Kokoda District, Tarof Village, South Sorong with the approach of learning media variables, reading interest and teacher performance. From the results of the research and test results with a multiple linear regression approach, the results of learning media and reading interest simultaneously influence teacher performance, while in the T test learning media does not significantly influence teacher performance and reading media significantly influences teacher performance. From the results of the moderation test, it was found that learning strategies do not moderate reading interest, while the most dominant variable influencing teacher performance is learning media. Based on the results of the analysis and discussion of research on the influence of learning media and reading interest on teacher performance with learning strategies as a moderating variable in Kokoda District, Tarof Village, South Sorong, several important things can be concluded. First, learning media and reading interest simultaneously have been shown to have a significant effect on teacher performance. This finding shows that teacher performance is the result of synergy between external factors in the form of the availability and utilization of learning media and internal factors in the form of teacher reading interest. The combination of these two variables is able to create a more effective and professional learning process.